The king's man [videorecording (DVD)] - Vaughn, Matthew, 1971-; Gajdusek, Karl; Fiennes, Ralph; Arterton, Gemma; Ifans, Rhys, 1967-; Goode, Matthew, 1978-; Hollander, Tom, 1967-; Dickinson, Harris, 1996-; Brühl, Daniel, 1978-; Hounsou, Djimon, 1964-; Dance, Charles; Millar, Mark (20th Century Studios, 2022)
The world on the brink of World War I is being manipulated by a cabal of political villains strategically placed to create conflict. One British lord and his son create a network of domestic worker spies in hopes of undermining the efforts, taking on the likes of Rasputin and Mata Hari with the crown's silent support. When the war happens anyway and takes the life of one of these men, the other must rise above his grief to bring an end to years of senseless deaths.